The Diversity and Abundance of Egg Parasitoids in Brown Planthopper, Nilaparvata lugens Stål. (Hemiptera: Delphacidae) at Different Rice Growth Phases in Saketi, Pandeglang, Banten - Nurullah Asep Abdilah; Hadi Susilo (Universitas Gadjah Mada, 2020)
An extensive study about egg parasitoid biodiversity in different plant growth stages is an important need. This study was aimed to determine the diversity and abundance of egg parasitoids Nilaparvata lugens on different rice growth stages in Saketi, Pandeglang, Banten. The parasitoids sample was collected three times with two days interval sampling in three villages, i.e. Sodong (location I), Sindanghayu (location II), and Sukalangu (location III) from February to September 2018. Ten plants (as bait: rice that infected by N. lugens eggs) were put during two days along the transect line (100 meters) with 10 m space in between. The findings revealed that the abundance richness (S), the diversity index (H'), and similarity (J') of egg parasitoids of N. lugens were higher in the location I than those in the locations II and III. The study indicated that the diversity and abundance of egg parasitoids of N. lugens decreased in the generative phase of rice growth.